Mountain Disasters and Rescue Mechanism in Nepal - Shahi, Ramesh Vikram (Journal of APF Command and Staff College, 2021)
Geographically, Nepal is divided into three regions, namely; the Terai, the hills, and the mountains. Nepal is prone to many types of disasters due to the various causes and one of the main causes is its geographic setting. Some disasters and hazards are prevalent to all over the country, some are area specific. Mountain and high altitude hazards are unique in nature and have distinct features and they pose several challenges for the rescue and relief operations. Disasters in mountain regions of Nepal have multi-dimensional effects on human life, property and the environment. The paper analyzes the mountain disasters, their nature and their impacts. It also focuses on the institutional as well as legal arrangements regarding disaster rescue. For this purpose, a qualitative descriptive and analytical method is applied to achieve the desired objectives of the study. This paper depends upon the secondary source of data available in several works of literature; journal articles, books, news articles, government reports, and websites. The paper finds that the frequencies of mountain disasters are low in comparison to other parts of Nepal, but they are diverse and complex. There are institutional and legal mechanisms for disaster risk reduction, but they are not adequate to respond mountain disasters effectively. All security agencies along with private sectors involving in mountain search and rescue operations do not have sufficient mountain-specific rescue units, training, and logistics.